PELATIHAN PENINGKATAN KETRAMPILAN MICROSOFT OFFICE BAGI SISWA SMP PGRI BLUNGUN - Wahyusari, Retno; Sulistiyo, Yogi; Nagari, Bintang Putra; Rahmasari, Nagita; Al Hadi, Fahreza; Ayu, Anggi Mutia; Masuri, Masuri; Mudjijanto, Mudjijanto; Widyassari, Adhika Pramitha (STIE Pelita Nusantara, 2024)
SMP PGRI Blungun has a computer practice room which is only used for computer-based national exams (UNBK). This condition is very unfortunate to see that there are Skills/Information and Communication Technology lessons. In this lesson the teacher only provides theory without any practical work. Success in education is supported by computer skills or digital literacy. It cannot be denied that information and communication technology is a primary need for many groups. Training on the introduction and use of Microsoft Office (MS Word, MS Excel, and MS Power Point). This is one of the computer skills activities that can prepare you for entering the world of work. As a result of the training, students were able to operate MS Word, MS Excel, and MS Power Point, where previously students had never operated Microsoft Office. The training also produces practicum modules that can be used by students to improve skills, as well as increase students' interest in learning to use computers or digital literacy.